2014
DOI: 10.1371/journal.pone.0106883
|View full text |Cite
|
Sign up to set email alerts
|

Cross Dimerization of Amyloid-β and αSynuclein Proteins in Aqueous Environment: A Molecular Dynamics Simulations Study

Abstract: Self-assembly of the intrinsically unstructured proteins, amyloid beta (Aβ) and alpha synclein (αSyn), are associated with Alzheimer’s Disease, and Parkinson’s and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between Aβ and αSyn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 91 publications
1
31
0
Order By: Relevance
“…4345 According to ref., 33 sampling during several hundred nanoseconds of aMD simulation is equivalent to sampling in the millisecond time scale for conventional MD (cMD) simulations, suggesting that we should be able to extend the sampling efficiency by several orders of magnitude with aMD. Of note, the aMD approach was recently used to analyze the larger Aβ-αSyn co-assembly system, 46 thereby justifying the suitability of this approach for Aβ42 dimer simulation.…”
Section: Resultsmentioning
confidence: 99%
“…4345 According to ref., 33 sampling during several hundred nanoseconds of aMD simulation is equivalent to sampling in the millisecond time scale for conventional MD (cMD) simulations, suggesting that we should be able to extend the sampling efficiency by several orders of magnitude with aMD. Of note, the aMD approach was recently used to analyze the larger Aβ-αSyn co-assembly system, 46 thereby justifying the suitability of this approach for Aβ42 dimer simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have asserted that these salt-bridges contribute to the stabilization of PrP C and that their abolition, either due to protonation of the acidic amino acids in response to low pH or by relevant genetic mutations, decreases the stability of PrP C and favors misfolding. [78][79][80][81] Thus, the overall destabilization of the salt bridge network in Y149F may be commensurate with a higher local desolvation barrier resulting from the increased hydration accompanying the dynamical instability in this system. 7a-c, we depict distributions of the salt bridge distances (d SB ) between each pair in the WT and the perturbed Y149F system.…”
Section: Inter-domain Salt Bridge Stabilitymentioning
confidence: 99%
“…The systems showed a lack of convergence ( Figure 12). It has been recently shown that the cross-dimerisation of IDPs reduces the RMSF of the peptide [41]. The calculations in quasi harmonic approximations are based on the motions of the macromolecules and not take into account the self-entropy due to rotation, translational and conformational changes of the molecule [42].…”
Section: Conformational Entropy Analysismentioning
confidence: 99%